ANALISIS AKURASI MODEL ZMIJEWSKI, SPRINGATE, OLHSON DAN GROVER UNTUK MEMPREDIKSI FINANCIAL DISTRESS KLUB SEPAK BOLA - Anasia Fathiyati Mutoharoh; Andria Referli; Milka Susana Theorupun (EKOBIS, 2021)
Financial distress is a condition where the company's financial performance declines which is indicated by negative net income accompanied by an increase in total liabilities. To avoid bankruptcy, it is necessary to have a prediction analysis of financial difficulties. The purpose of this study is to examine which financial difficulty prediction model is the most accurate to be applied to clubs that have joined in the Uefa Champions League. Determination of the research sample using purposive sampling method with a population of 93 European Champions League clubs for the 2011 - 2020 season for the 2016 - 2020 research period and obtained as many as 80 samples and grouped into two categories, namely financial distress and non-financial distress. The data analysis method is using the model accuracy test by comparing the results of the prediction model calculations with the sample categories and considering the results of the type I and II error levels. The error rate I is generated from the sum of prediction errors which in fact experience financial distress but the prediction results are non-financial distress and vice versa for type II error. The results of this study indicate that the Zmijewski model is the model with the highest level of accuracy for predicting the financial distress of football clubs that have competed in the Uefa Champions League with an accuracy rate of 71% with type I error of 44.83% and error type II of 19. 61%.